PENGARUH MEDIA PEMBELAJARAN VIRTUAL REALITY SAINS UNTUK MENINGKATKAN PEMAHAMAN SISWA PADA MATA PELAJARAN IPAS DI SDN GILI ANYAR - Abdussalam; Pratiwi, Siska; Yuniarti, Diah Retna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
To do well in a class, you must make sure you understand the material thoroughly. However, there will be times when certain students at SDN Gili Anyar have difficulty grasping the material, especially in the science sessions. This study aims to examine the effectiveness of virtual reality (VR) learning resources in enhancing scientific education at SDN Gili Anyar. The research followed the standard procedure for quantitative studies by using a one-group pretest-posttest design. The significance level of 0.000, which is lower than the recognized threshold of 0.05, was shown by the results of the comprehension assessment's paired sample t-test. Students' understanding of scientific concepts is significantly enhanced by the virtual reality-based science learning medium at SDN Gili Anyar.